1996
DOI: 10.1002/(sici)1520-6769(199609)19:2<91::aid-nrc168>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

The combined control of locomotion and prehension

Abstract: This study investigated the strategies used by individuals when the locomotor and prehensile motor systems are used simultaneously. Subjects were required to perform five tasks: to walk normally, walk and pick up a small object, walk and pick up a large object, and finally pick up small and large objects from a standing position. The general organization and control of lower limb movements was largely unaffected by the introduction of reaching movements. However, arm movements were generated faster when subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 13 publications
2
8
2
3
Order By: Relevance
“…Lifting an object while standing can be done more easily while standing on the foot ipsilateral to the lifting hand than while standing on the foot contralateral to the lifting hand (Carnahan, McFadyen, Cockell, & Halverson, 1996). When one walks, one's hands and feet normally move in a contralateral (anti-phase) rather than ipsilateral (in-phase) fashion.…”
Section: Experiments 5 Andmentioning
confidence: 99%
“…Lifting an object while standing can be done more easily while standing on the foot ipsilateral to the lifting hand than while standing on the foot contralateral to the lifting hand (Carnahan, McFadyen, Cockell, & Halverson, 1996). When one walks, one's hands and feet normally move in a contralateral (anti-phase) rather than ipsilateral (in-phase) fashion.…”
Section: Experiments 5 Andmentioning
confidence: 99%
“…An interesting problem presents when grasping takes place simultaneously with locomotion, requiring the coordination of these two modes of control [ 14 , 76 78 ]. More specifically, the effect of constraint of the joints of the upper limb was studied to shed light on the mechanisms of stabilization of manually held objects during walking through impedance adjustments [ 14 ].…”
Section: Concept Of Mechanical Impedancementioning
confidence: 99%
“…The combined task of walking and reaching-to-grasping (i.e., prehension) an object has been studied in young adults. [52][53][54][55][56] An important aspect of these studies is that walking and prehension are mutually modified to accommodate the execution of the manual task. In older adults, Delbaere and colleagues 57 observed that older adults often avoid performing the combined task of reaching for an object while walking.…”
Section: Upper Limb Control In Faller and Non-faller Older Adultsmentioning
confidence: 99%